Kajian Normatif Pertanggung Jawaban Pidana Pada Pelaku Prostitusi Online - Akristianto Ahmad; Nurmin K. Martam; Robby W. Amu (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Abstract. The development of the era has driven various changes in the order of human life and forced humans to develop in a more advanced and modern life. As one proof that the development of the era is the increasingly advanced and sophisticated information technology that can be easily learned, accessed and utilized to support humans in carrying out their daily lives. The progress and sophistication of this technology has now had a great impact on life both in the socio-economic and socio-cultural aspects of society. society can easily utilize the sophistication of this technology wisely or it can also be misused. Crimes that often occur using online media are crimes in the form of online prostitution. The problem approach method used in this writing is the normative juridical method. Primary data collection techniques are obtained by conducting searches, inventories and reviewing regulations using literature studies including laws and regulations, books and articles in journals and scientific works. Criminal law enforcement against online prostitution in Indonesia still faces various obstacles. Criminal law enforcement against online prostitution in Indonesia is legally based on Law No. 1 of 2003 concerning Information and Electronic Transactions. 19 of 2016), Criminal Code, and Pornography Law No. 44 of 2008.